Integrated Nutrient Management for Tomato-Okraindian Spinach Cropping Pattern - Noor, S; Shil, NC; Uddin, MM; Alam, MK (Bangladesh Journal of Agricultural Research, 2012)
Field experiment on Tomato-Okra-Indian spinach cropping pattern was conducted at a farmers homestead of Tangail (AEZ 8) during 2007-08 and 2008-09 to find out a suitable combination of chemical fertilizers and organic manure for sustainable crop yield. There were 5 treatments comprising different percentages of the recommended chemical fertilizers (RCF) with two levels (0 and 5 t/ha) for tomato and three levels (0, 2.5 and 5 t/ha) for okra each of poultry manure and cowdung. No organic manure was used for the third crop Indian Spinach. The treatments were arranged in Randomized Complete Block Design with four replications. An amount of 75% dose of RCF (N150P40K80S20Zn2B1 kg/ha) along with poultry manure @ 5 t/ha appeared as the best suited combination providing tomato yield 95.3 t/ha and 88.2 t/ha for the first year and second year, respectively. Again, an amount of 75% dose of RCF(N120P35K70S15Zn2B1 kg/ha) along with poultry manure @ 2.5 t/ha appeared as the best package providing the highest okra yield (15.03 t/ha and 12.98 t/ha). The highest yield (36.3 t/ha and 33.7 t/ha for the first and second year, respectively) of Indian Spinach was recorded from (75% recommended N + PM residue), which was statistically identical with (100 % recommended N), but significantly higher over rest of the treatments. Poultry manure performed better over cow dung. A package of 75% recommended chemical fertilizer along with 5 t PM/ha appeared as the best suited combination providing higher yield and economic return. DOI: http://dx.doi.org/10.3329/bjar.v36i4.11747 Bangladesh J. Agril. Res. 36(4): 595-603, December 2011